2018
DOI: 10.1038/s41598-018-36681-w
|View full text |Cite
|
Sign up to set email alerts
|

The mineralocorticoid receptor is essential for stress axis regulation in zebrafish larvae

Abstract: The mineralocorticoid receptor (MR) in mammals mediates the effects of aldosterone in regulating fluid balance and potassium homeostasis. While MR signalling is essential for survival in mammals, there is no evidence that MR has any physiological role in ray-finned fish. Teleosts lack aldosterone and emerging evidence suggest that cortisol mediates ion and fluid regulation by activating glucocorticoid receptor (GR) signalling. Consequently, a physiological role for MR signalling, despite its conserved and anci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
103
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 85 publications
(114 citation statements)
references
References 50 publications
(77 reference statements)
9
103
2
Order By: Relevance
“…Previous reports using knockout fish models indicate that MR plays an important role in regulating HPI axis function (Faught & Vijayan, ) and stress‐related behaviour (Sakamoto et al . ; Faught & Vijayan, ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous reports using knockout fish models indicate that MR plays an important role in regulating HPI axis function (Faught & Vijayan, ) and stress‐related behaviour (Sakamoto et al . ; Faught & Vijayan, ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports using knockout fish models indicate that MR plays an important role in regulating HPI axis function (Faught & Vijayan, ) and stress‐related behaviour (Sakamoto et al . ; Faught & Vijayan, ). In combination with mammalian work (Joëls & de Kloet, ), this suggested that the primary role for this receptor may have been in stress sensing and appraisal prior to its mineralocorticoid role in the tetrapod lineage (Baker et al .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations